1987
DOI: 10.1111/j.1475-6765.1987.tb00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Working‐class authoritarianism: a re‐examination of the Lipset thesis

Abstract: Abstract. Almost thirty years ago Lipset published his well‐known article ‘Democracy and working‐class authoritarianism’. His central thesis is that the working class more than other social classes, is predisposed to authoritarian and anti‐democratic attitudes. Several authors have criticized this thesis, especially by questioning Lipset's concept of democracy. Our approach is somewhat different in that in our opinion Lipset's conceptualization and measurement of social class is inaccurate and inappropriate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 17 publications
3
43
1
Order By: Relevance
“…The working class authoritarian model has been tested in many contexts with mixed results. Most later studies have concluded that it is education, not an occupationor income-based measure of class, that is most closely associated with support for intolerance, racism, extreme nationalism, and right-wing parties (Lipsitz 1965;Grabb 1979;Dekker and Ester 1987). If the concept of class is respecified to include education, however, the model becomes more successful in accounting for empirical phenomena such as lower-class support for conservative or authoritarian ideas, parties or movements, as well as in accounting for the decline in class voting (e.g.…”
Section: Theoretical Accounts Of the Trump Coalitionmentioning
confidence: 99%
“…The working class authoritarian model has been tested in many contexts with mixed results. Most later studies have concluded that it is education, not an occupationor income-based measure of class, that is most closely associated with support for intolerance, racism, extreme nationalism, and right-wing parties (Lipsitz 1965;Grabb 1979;Dekker and Ester 1987). If the concept of class is respecified to include education, however, the model becomes more successful in accounting for empirical phenomena such as lower-class support for conservative or authoritarian ideas, parties or movements, as well as in accounting for the decline in class voting (e.g.…”
Section: Theoretical Accounts Of the Trump Coalitionmentioning
confidence: 99%
“…On the contrary, there is abundant empirical evidence that education reduces authoritarianism (cf. Adorno et al, 1950Adorno et al, /1982Christie, 1954;Selznick and Steinberg, 1969;Quinley and Glock, 1979;Dekker and Ester, 1987). The most sophisticated interpretation of this relationship stems from Gabennesch (1972).…”
Section: Social Determinants O F Authoritarianismmentioning
confidence: 99%
“…And although sociologists following Lipset (1959) ascertained an empirical relationship between social class and education on the one hand and phenomena related to authoritarianism on the other hand, they failed to interpret this re lationship from a consistent theoretical perspec tive, with some exceptions (cf. overviews by Dekker and Ester, 1987;Scheepers, Eisinga and Van Snippenburg, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the antecedents of economic progressiveness lie in trying to reduce economic insecurity, the antecedents of cultural conservatism lie in trying to reduce cultural insecurity. Empirical studies show that an emphasis on order and on strong authority is grounded in feelings of discontent (anomia) (see for example, Blank 2003;Eisenga and Scheepers 1989;Lutterman and Middleton 1970;McDill 1961;Roberts and Rokeach 1956;Srole 1956) and that this is prevalent among those with little cultural capital (the lower educated) and not among those with ample cultural capital (the higher educated) (e.g., Dekker and Ester 1987;Grabb 1979;Grabb 1980;Houtman 2001Houtman , 2003Houtman , 2004.…”
Section: Social Position Economic and Cultural Insecuritymentioning
confidence: 99%